Advancements and trends in exosome research in lung cancer from a bibliometric analysis (2004-2023) - Zhong, Wen; Zhao, Xiaofei; Zhang, Xiabiao; Xu, Yiwen; Liu, Mengqian; Yang, Xiaoyun; Jiang, Yi; Shen, Xiaozhu (Frontiers in Oncology, 2024)
Background: Lung cancer, characterized by its high morbidity and lethality, necessitates thorough research to enhance our understanding of its pathogenesis and discover novel therapeutic approaches. Recent studies increasingly demonstrate that lung cancer cells can modulate the tumor microenvironment, promoting tumor growth, and metastasis through the release of exosomes. Exosomes are small vesicles secreted by cells and contain a variety of bioactive molecules such as proteins, nucleic acids, and metabolites. This paper presents a comprehensive review of exosome research in lung cancer and its progress through bibliometric analysis.Methods: Publications related to exosomes in lung cancer patients were systematically searched on the Web of Science Core Collection (WoSCC) database.Bibliometric analysis was performed using VOSviwers, CiteSpace, and the R package "Bibliometrics". Publications were quantitatively analyzed using Microsoft Office Excel 2019. The language of publication was restricted to "English" and the search strategy employed TS=(exosomes or exosomes or exosomes) and TS=(lung cancer).